Lakes and streams as sentinels of environmental change in terrestrial and atmospheric processes. Issue 5 (1st June 2008) - Williamson, Craig E; Dodds, Walter; Kratz, Timothy K; Palmer, Margaret A
Abstract : Recent advances in our understanding of the importance of continental‐ to global‐scale connectivity among terrestrial and aquatic ecosystems make consideration of aquatic–terrestrial linkages an urgent ecological and environmental issue. Here, we describe the role of inland waters as sentinels and integrators of the impact of humans on terrestrial and aquatic ecosystems. The metabolic responses of lakes and streams (ie the rates at which these systems process carbon) are proposed as a common metric to integrate the impacts of environmental change across a broad range of landscapes. Lakes and streams transport and alter nutrients, contaminants, and energy, and store signals of environmental change from local to continental scales over periods ranging from weeks to millennia. A carefully conceived and well‐integrated network that includes monitoring and experimental approaches to terrestrial–aquatic connectivity is critical to an understanding of basic ecosystem‐level processes and to forecasting and mitigating future environmental impacts at the continental scale.